We're rich!! Or are we? Oil and development in S\~ao Tomé e Príncipe - Steven Kyle (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2003)
This paper discusses the policy issues facing S\~ao Tomé e Príncipe, given the discovery and imminent exploitation of large reserves of oil in its territorial waters. A common reaction to news of a large oil discovery is to think that all economic problems can be solved by the flow of oil revenues. However, the experience of numerous oil countries shows that it is necessary to temper this attitude somewhat since there are numerous pitfalls which can offset the positive aspects of oil riches. An appropriate policy for macro balance and for disposal of oil revenues will be essential if S\~ao Tomé e Príncipe is to avoid the problems which have plagued countries such as Nigeria or Angola. The two main lessons of macroeconomics in such a situation is first not to generate revenue faster than it can be productively used and second to invest in such a manner that the country's underlying comparative advantages are preserved. In the case of S\~ao Tomé e Príncipe, history and recent analyses confirm that there is a strong comparative advantage in agriculture, implying that investments which enhance productivity and efficiency in this sector would be appropriate for expenditure of oil revenues. In addition, such a strategy would have beneficial effects in terms of poverty alleviation and equitable distribution of benefits from the coming windfall.
Keywords: 330; Erdölförderung; Entwicklungspolitik; Entwicklungsstrategie; Sao Tome und Principe